Bridges between the 3-dimensional elementary almost contact metric structures - Beldjilali, Gherici (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 515.1 We construct all possible bridges between the three-dimensional elementary almost contact metric structures. Accordingly, starting from any structure of any class, we can construct an unlimited number of structures of any other class. Specific examples are presented.